KESADARAN KEAMANAN DAN PRIVASI DATA PENGGUNA WHATSAPP (STUDI KASUS DI PROVINSI JAWA BARAT) - Tristania Pangaribuan; Diana Sari; Caecilia Suprapti Dwi Takariani; Oktolina Simatupang (BPSDMP Kominfo Jakarta, 2023)
Social media applications provide convenience with the features available but can also cause problems, such as security and privacy, in their use, which is also possible in WhatsApp. The condition of security and privacy awareness among WhatsApp users can be an illustration of how users are aware of minimizing various kinds of risks that can arise when using WhatsApp. This study provides an overview of WhatsApp usage, security awareness, and privacy data from respondents, and sociodemographic relationships with the synthesis framework of data security and privacy in WhatsApp usage. The study was conducted quantitatively, with WhatsApp users in West Java Province serving as the unit of analysis and the locus. The questionnaire instrument was distributed online through time sampling within a certain period and accidental sampling. The results of the study provide an overview of WhatsApp usage. The perspective on data security and privacy in West Java Province also shows that many respondents have this awareness. The relationship between sociodemographic variables and the use of WhatsApp shows significant results in several main areas, namely the information security area, the perceived mobile apps area, the perceived control area, and the disclosure information detection area.